Análisis a los Estados Financieros Del Gobierno Autónomo descentralizado Provincial de Zamora Chinchipe, correspondiente al periodo 2013 - 2014 - González Silva, Mafalda Germania (2016)
This thesis was carried out in order to meet prior to obtaining the engineering degree in Accounting and Auditing , CPA at the National University of Loja requirement , the present study it conducted in order to determine the economic position financial and Provincial Government of Zamora Chinchipe , which allowed provide valid information for the correct and timely decision making. As for its implementation were complied with the proposed objectives ie has made the respective financial interpretation to the financial statements of the aforementioned public institution of the Province of Zamora Chinchipe, for which different methods of financial analysis was applied to be the horizontal method, which agreed to perform the respective comparisons both assets, liabilities and equity for the years 2013 and 2014 under study and it required the use of Balance Sheets and Income Statements, also the vertical method was used to percentage determine the involvement of each of the accounts in order to determine which account is the one with greater representation concluding that are long-lived investments in its execution, certain financial ratios is also used as liquidity, indebtedness and profitability, which indicate the economic and financial position that is this important public institution of the Ecuadorian Amazon. The result of the investigation conducted disclosed favorable situations like having more control of assets, liabilities and expenses and unfavorable for the institution since at the time not to conduct financial analysis the company runs the risk of making decisions that can affect normal development; why the implementation of corrective measures proposed by formulating recommendations to improve the appropriate use of economic resources and prevent scenarios that could affect the stability of the aforementioned institution , by implementing appropriate controls are present allow inmates to monitor and ensure compliance objectives.